2023
DOI: 10.15244/pjoes/158147
|View full text |Cite
|
Sign up to set email alerts
|

The Environment Education Policy in Behavior Commitment of Stakeholders for the Environmental Sustainability

Abstract: Implementation of environmental education is an important policy to preserve the environment. The authors believe that stakeholders' involvement is significant for the long-term sustainability of ecological and conservation efforts. The purpose of the study was to discuss the commitment of environmentally sound education policymakers to preserve the environment. We have searched and analyzed data from many published books, environmental journals, and environmental education documents from international ecologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…Finally, the suggestion to involve children in continuous energy conservation campaigns presents a unique opportunity for long-term impact. Policymakers might consider integrating sustainability education into school curricula and launching campaigns that empower children to play active roles in promoting energy-saving practices within their families (Gani et al ., 2023). This approach not only educates the current generation but also influences future behaviors.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…Finally, the suggestion to involve children in continuous energy conservation campaigns presents a unique opportunity for long-term impact. Policymakers might consider integrating sustainability education into school curricula and launching campaigns that empower children to play active roles in promoting energy-saving practices within their families (Gani et al ., 2023). This approach not only educates the current generation but also influences future behaviors.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…To verify the influence mechanism of media attention on corporate ESG performance, this study constructed regression model 1, as shown in equation (1), where dependent variable ESG is corporate ESG performance, independent variable is media attention. The regression model is:…”
Section: Model Constructionmentioning
confidence: 99%
“…With the rapid development of the Internet era, the media has an important impact on corporate governance and operating activities in the process of promoting companies to improve corporate ESG performance and sustainability [ [1]]. Specifically, on the one hand, the media has an external governance role and can supervise the behavior of companies, promote companies to actively improve environmental pollution problems, take the initiative to assume social responsibilities, solve corporate governance problems in a timely manner, and urge companies to pay attention to their own ESG performance [ [2]].…”
Section: Introductionmentioning
confidence: 99%
“…until the final stage of processing. Therefore, so that the implementation of one of the waste handling processes can run smoothly, knowledge is needed in maintaining environmental balance and the need for habits that must be taught to all individuals from an early age (Gani et al, 2023;Siregar et al, 2021;.…”
Section: Introductionmentioning
confidence: 99%